Relationship Between the Cochlear Aqueduct and Internal Auditory Canal: Surgical Implications for Transcanal Transpromontorial Approaches to the Lateral Skull Base. Issue 2 (February 2021) - Molinari, Giulia; Yacoub, Abraam; Bonali, Marco; Wimmer, Wilhelm; Alicandri-Ciufelli, Matteo; Caversaccio, Marco; Presutti, Livio; Anschuetz, Lukas
Abstract : Hypothesis: The cochlear aqueduct (CA) is subject to considerable anatomical variability. We hypothesize a topographical relationship between the CA and the internal auditory canal (IAC). Background: The CA represents the lower limit of dissection during transcanal transpromontorial approaches to the lateral skull base due to its close relationship to the lower cranial nerves and jugular vein. Methods: Three-dimensional models from high-resolution computed tomography scans of normal human temporal bones were created using threshold-based segmentation. The CA was classified into four categories. Five points were determined on the three-dimensional models to measure the surgically relevant relationships. Results: Segmentation was performed on 26 high-resolution computed tomography scans. The average length of the virtual and visual part of the CA was 6.6 mm (SD ±1.7 mm) and 5.5 mm (SD ±1.3 mm) respectively. The mean distance between the IAC and the medial end of the visual part of the CA was 3.8 mm (±0.7 mm), while the average distance between the IAC and the lateral end was 1.4 mm (±0.6 mm). The distance between the visual part of the CA and the IAC increased by 0.25 mm per from the fundus of the IAC. Conclusion: A close relationship between the CA and the IAC could be established, despite the anatomical variability of the CA. The distance between CA and IAC increases by 0.25 per mm from the fundus to the porus of the IAC. These findings quantify the inferior limit of dissection of the transcanal transpromontorial approach to the lateral skull base.